On a family of inverse curvature flows for closed convex plane curves. (December 2019) - Guo, Hongxin; Sun, Zezhen
Abstract: In this note we introduce a family of flows for closed convex curves in the plane. Along the flows the enclosed area of the curve is increasing, and the curve remains convex and converges to a circle. The flows include various flows studied by various authors as special cases.